An investigation into the effects of inorganic toxins and tryptophan metabolites on the forebrain cholinergic system and the pineal gland of the rat - Mahabeer, Rajeshree (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1997)
As soon as the building of the body is completed, the ageing process begins. In the natural course of events, the functioning of some organ systems finally ebbs below the threshold necessary to maintain the body, resulting in death. This occurrence is relatively rare, because diseases superimpose themselves upon the ageing process, bringing premature death resulting from pathological causes. This study focused on the cholinergic system of the rat forebrain. The cholinergic neurons in the brain are said to be involved in memory and learning, and a decrease in the activity of its enzymes has been reported in certain diseases, such as Alzheimer's disease. In the present study, the in vitro effects on the cholinergic system, of aluminium and mercury and tryptophan metabolites, kynurenic acid and quinolinic acid, are determined. Aluminium has been considered as a possible factor in Alzheimer's disease. Mercury in high concentrations is toxic, and its use in amalgam for dental treatment is under consideration with regard to its possible role in promoting neurological disease. The tryptophan metabolites increase in the brain with age and may have a role in pathological diseases. Quinolinic acid, when administered in toxic concentrations produces a possible model for Huntington's disease. This study investigated the effects of the above mentioned toxins on: (1) The synthesis of acetylcholine by choline acetyltransferase; (2) The specific binding of acetylcholine muscarinic receptors; (3) The degradation of acetylcholine by acetyl cholinesterase, Choline acetyltransferase activity did not change in the presence of aluminium chloride, kynurenic acid and quinolinic acid from 1 nM to 1 mM. Mercuric chloride had no significant effect on the enzymes activity from a concentration of 1 nM- 1 pM. At 10 pM there was a significant decrease in cholineacetyltransferase activity (P < 0.001). Enzyme activity continued to decrease at 100 pM (P < 0.0002). At 1 mM, enzyme activity was virtually non existent (P < 0.0001). Acetyl cholinesterase activity was not affected by aluminium chloride, kynurenic acid and quinolinic acid. Mercuric chloride from 1 pM - 1 mM significantly reduced the enzyme activity (P < 0.05). The binding of the antagonist, [Â³H] quinuclidinyl benzilate (QNB), to acetylcholine muscarinic receptors, revealed that aluminium chloride did not affect the binding of the antagonist, in the concentration range of 1 nM - 100 pM, to the receptors. At 1 mM, aluminium chloride appears to increase the sensitivity of the receptors for the ligand (P < 0.01). Mercuric chloride also does not appear to have any significant effect on receptor binding in this range. However, at 1 mM there appears to be a very significant decrease in receptor binding (P < 0.01). This decrease may be attributed to the interaction of mercury with the sulfhydryl groups in muscarinic receptors. Kynurenic acid had no effect on the receptor binding. Quinolinic acid, in the concentration range from 10 nM - 1 mM increased the binding ofthe receptor to [3Hi QNB significantly (P < 0.001). The study also investigated the effect of the tryptophan metabolites of the kynurenine pathway on pineal indole metabolism. The kynurenine pathway is a major route of tryptophan metabolism in the pineal gland, along with indole metabolism. Investigations showed that kynurenic acid produced a decrease in N-acetylserotonin concentrations ( P < 0.001) and melatonin concentrations (P < 0.003). Further experiments using quinolinic acid produced a similar decrease in N-acetylserotonin (P < 0.001) and melatonin (P < 0.015). A decrease was also noted in the level of 5-methoxytryptophol (P < 0.0005). These findings suggest that aluminium chloride, kynurenic acid and quinolinic acid have no possible role in the decrease of activity of cholinergic enzymes which is observered in diseases such as Alzheimer's disease. The results regarding the effect of mercury chloride on the cholinergic system suggest that low exposure to the toxin will not adversely effect the enzymes. The decrease in N-acetylserotonin and melatonin concentrations reported here, may be a result of kynurenic acid and quinolinic acid having an inhibitory effect on the enzyme, serotonin Nacetyltransferase, which is responsible for the conversion of serotonin to N-acety/serotonin.
Keywords: Toxins -- Physiological effect; Metabolites -- Physiological effect; Pineal gland; Brain -- Physiological aspects